Cardiac patient care during a pandemic: how to reorganise a heart failure unit at the time of COVID-19. (July 2020) - Agostoni, Piergiuseppe; Mapelli, Massimo; Conte, Edoardo; Baggiano, Andrea; Assanelli, Emilio; Apostolo, Anna; Alimento, Marina; Berna, Giovanni; Guglielmo, Marco; Muratori, Manuela; Susini, Francesca; Palermo, Pietro; et al.
To date, the pandemic spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has involved over 100 countries in a matter of weeks, and Italy suffers from almost 1/3 of the dead cases worldwide. In this report, we show the strategies adopted to face the emergency at Centro Cardiologico Monzino, a mono-specialist cardiology hospital sited in the region of Italy most affected by the pandemic, and specifically we describe how we have progressively modified in a few weeks the organization of our Heart Failure Unit in order to cope with the new COVID-19 outbreak. In fact, on the background of the pandemic, cardiovascular diseases still occur frequently in the general population, but we observed consistent reduction in hospital admissions for acute cardiovascular events and a dramatic increase of late presentation acute myocardial infarction. Despite a reduction of healthcare workers number, our ward has been rearranged in order to take care of both COVID-19 and cardiovascular patients. In particular according to a triple step procedure we divided admitted patients in confirmed, suspected and excluded cases (respectively allocated in "red", "pink" and "green" separated areas). Due to the absence of definite guidelines, our aim was to describe our strategy in facing the current emergency, in order to reorganize our hospital in a dynamic and proactive manner. To quote the famous Italian writer Alessandro Manzoni 'It is less bad to be agitated in doubt than to rest in error.'